Revision of the rhinoceros beetle genus Oryctophileurus Kolbe with description of a new species, the male of O. varicosus Prell, and notes on biogeography (Scarabaeoidea, Dynastinae, Phileurini) - Robert Perger; Paschoal Grossi (ZooKeys, 2013)
The genus Oryctophileurus is reviewed and its validity is supported by a combination of the following apomorphic characters: a single cephalic horn with lateral carina, pronotal cavity with ocellate punctures and two teeth or tubercles close behind the anterior pronotal margin. The male of Oryctophileurus varicosus Prell, 1934, is described for the first time. A new species, Oryctophileurus guerrai Perger & Grossi sp. n., from subhumid Tucuman-Bolivian forest in the Southern Bolivian Andes is described. The new species is distinguished from its closest relative, O. armicollis Prell, 1911, by a narrower distance between the inner teeth of the dorsal pronotal protuberances and a reduced area of weakly developed ocellate punctures above the posterolateral pronotal margin. The occurrence of Oryctophileurus species in areas of endemism along the eastern slope of the tropical Andes suggests that these populations represent biogeographic “relicts”, and the discovery of Oryctophileurus guerrai sp. n. in the southern Bolivian Andes suggests that this area is underrated with respect to insect diversity and endemism.